2021
DOI: 10.1111/dth.15031
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidities of bullous pemphigoid: A single‐center retrospective case–control study from Turkey

Abstract: Although significant associations between bullous pemphigoid (BP) and certain comorbidities, primarily subtypes of neurological disorders, have been reported in several populations, it has yet to be demonstrated whether a correlation exists between pre‐existing comorbidities and serum titers of anti‐BP180 and 230 immunoglobulin G (IgG) antibodies among BP patients. The aim of the current study is to investigate the demographic and clinical features of BP patients in a large series from Turkey, determine the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 36 publications
1
13
1
Order By: Relevance
“…[15][16][17][18] On the contrary, some researchers have demonstrated similar dementia rates in BP patients and controls. 10,[19][20][21] We did not observe Alzheimer MRI patterns in these patients, nor did we find such pattern in the control group. There are contradictory results in terms of the association between BP and Alzheimer's disease in the literature.…”
Section: Discussioncontrasting
confidence: 79%
See 2 more Smart Citations
“…[15][16][17][18] On the contrary, some researchers have demonstrated similar dementia rates in BP patients and controls. 10,[19][20][21] We did not observe Alzheimer MRI patterns in these patients, nor did we find such pattern in the control group. There are contradictory results in terms of the association between BP and Alzheimer's disease in the literature.…”
Section: Discussioncontrasting
confidence: 79%
“…Conversely, Papakonstantinou et al reported a lower prevalence of Alzheimer's disease in BP patients in comparison with the control group 23 . On the other hand, Kilic Sayar et al showed no difference in Alzheimer's disease between BP patients and controls 19 …”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Many previous studies have shown associations between BP and cardiovascular risk factors, suggesting a possible link between BP and MS. During the past decade, a number of case–control studies 9 , 10 , 19 22 have shown a strong association between BP and diabetes, whereas others have not. 23 28 Similarly, hypertension has been shown to be significantly associated with BP in many case–control studies, 19 24 , 29 but not under all circumstances. 9 , 10 , 25 27 A few studies have shown a negative association between hyperlipidemia and BP, 24 but others have not shown any relationship.…”
Section: Discussionmentioning
confidence: 93%
“… 23 28 Similarly, hypertension has been shown to be significantly associated with BP in many case–control studies, 19 24 , 29 but not under all circumstances. 9 , 10 , 25 27 A few studies have shown a negative association between hyperlipidemia and BP, 24 but others have not shown any relationship. 19 , 21 In addition, two large population-based studies conducted in the United States showed a significant association between obesity and BP.…”
Section: Discussionmentioning
confidence: 93%